2022
DOI: 10.3390/rs14174267
|View full text |Cite
|
Sign up to set email alerts
|

Spectral Indices as a Tool to Assess the Moisture Status of Forest Habitats

Abstract: Measurement of water content in forest habitats is considered essential in ecological research on forests, climate change, or forest management. In the traditional forest habitat classification, two systems of habitat conditions analysis are found: single factor and multifactor methods. Both are laborious and therefore costly. Remote sensing methods provide a low-cost alternative. The aim of the presented study was to find the relationship between the spectral indices obtained from satellite images and the for… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
1
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(5 citation statements)
references
References 41 publications
0
1
0
Order By: Relevance
“…The ecotype from Kampinoski National Park (2 and 3) was selected based on the results of Przybylski et al [2]. The National Park Bory Tucholskie (6) was chosen due to the results of Młynarczyk et al [15]. The "Rychtalska pine" ecotype (5) was chosen due to the results of Wójkiewicz et al [16] and Barzdajn [14].…”
Section: Research Areamentioning
confidence: 99%
See 2 more Smart Citations
“…The ecotype from Kampinoski National Park (2 and 3) was selected based on the results of Przybylski et al [2]. The National Park Bory Tucholskie (6) was chosen due to the results of Młynarczyk et al [15]. The "Rychtalska pine" ecotype (5) was chosen due to the results of Wójkiewicz et al [16] and Barzdajn [14].…”
Section: Research Areamentioning
confidence: 99%
“…Descriptions of the research areas were supplemented with a summary of atmospheric precipitation according to Muñoz Sabater [18]. [15], after testing 249 vegetation indices calculated according to the formulas stored and described in the "Index Database" (https://www.indexdatabase.de/, accessed on 28 December 2022), demonstrated that the NDVI can be used as an indicator describing both the moisture and trophic status of forest habitats. This was considered an important measure of habitat conditions, which simultaneously influences the condition of forest stands.…”
Section: Research Areamentioning
confidence: 99%
See 1 more Smart Citation
“…Yang used hyperspectral data to generate a visualization of the changes in anthocyanin content of litchi during storage [16]. Researchers have studied and constructed various vegetation indices [17][18][19][20], for example, the Difference Spectral Index (DSI), Ratio Spectral Index (RSI), and Normalized Difference Spectral Index (NDSI). Lopes modified DSI, RSI, and NDVI; combined linear, exponential, power, and logarithmic regression in the modeling process; and confirmed the feasibility of using the spectral index to estimate carotenoid and anthocyanin content in lettuce [21].…”
Section: Introductionmentioning
confidence: 99%
“…Global climate warming has contributed to landform transformation for decades (Song et al, 2018) and increasing average air temperatures have resulted in significant changes in regional climates and local ecosystems, thereby increasing the risks of fires, droughts, floods and landslides (Allen et al, 2010; Flannigan et al, 2009; Gariano & Guzzetti, 2016; Hirabayashi et al, 2013; Młynarczyk et al, 2022). In cold climate settings, the impact has been manifested as dynamic responses in glacial systems (Benn et al, 2012; Benn & Evans, 2010).…”
Section: Introductionmentioning
confidence: 99%